Implementación un banco de prueba tipo eólico para realizar mediciones con base en aerogenerador espiral de Arquímedes - Poveda Guatama, Erik Farley; Martínez Martínez, Osneider de Jesús (Universidad Antonio Nariño, 2024)
Wind turbines are one of the most important and promising renewable energy sources today. Wind energy is clean and produces no greenhouse gas emissions, making it a sustainable alternative to fossil energy sources. and covers an initiative for the energy transition in Colombia.